2015
DOI: 10.1007/s11325-015-1262-3
|View full text |Cite
|
Sign up to set email alerts
|

Elevated low-density lipoprotein cholesterol is independently associated with obstructive sleep apnea: evidence from a large-scale cross-sectional study

Abstract: We demonstrated that patients with OSA had a higher percentage of dyslipidemia than subjects without OSA. Of the various components in serum lipid, only LDL-C was independently associated with OSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 32 publications
1
31
0
Order By: Relevance
“…The detrimental effects of OSAS in patients with dyslipidemia have been well-documented. More patients with OSAS have dyslipidemia than subjects without OSAS, and only LDL-C is independently associated with OSAS 6 . CPAP treatment significantly decreases the TC level, with slight changes in TG, HDL, and LDL-C levels 7 .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The detrimental effects of OSAS in patients with dyslipidemia have been well-documented. More patients with OSAS have dyslipidemia than subjects without OSAS, and only LDL-C is independently associated with OSAS 6 . CPAP treatment significantly decreases the TC level, with slight changes in TG, HDL, and LDL-C levels 7 .…”
Section: Discussionmentioning
confidence: 96%
“…Standardized anthropometric parameters, including waist circumference (WC), hip circumference (HC) and neck circumference (NC), were measured using standard methods as described previously 6 . These anthropometric data were recorded as the mean of two measurements.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our large-sample-size study also confirms the positive association between the ApoB/ApoA-I and OSA and describes the nature of complex relationship between the two. One previous study showed that patients with OSA have independently elevated LDL, which decreased after adjustment for multiple factors [11,37]. Total ApoB reflects the number of total potentially atherogenic lipoprotein particles, and ApoA-I is involved in reverse cholesterol transport.…”
Section: Discussionmentioning
confidence: 99%
“…The SPOSA is a weighted model containing comorbidity and demographic variables known to be associated with OSA, including: chronic pulmonary disease [35], congestive heart failure [5, 6], diabetes [7], dyslipidemia [36, 37], hypertension [3, 38], atrial fibrillation [39, 40], liver disease [41], coronary artery disease [42], and pulmonary hypertension [43, 44]. The association between hemiplegia/paraplegia and OSA may be related to the an association between OSA and acute ischemic stroke [4, 45].…”
Section: Discussionmentioning
confidence: 99%